(3GdVQjHI Ydi CQHGM GdTQcGJ (BLI.B.S :s (3MSH JYOjdGJ bGfhf GdeGdjI (B2010 (3dWdHI GdeYGgO GdYdjG h GdLGeYGJ h cd GdeNJUHf GdGbJUGOjjf (B/s - (3Hf GYeGQg, efUhQs ((3GdLRGFQ(B: s (3OGQ gheg(B, s, 2010)
(3GdVQjHI Ydi CQHGM GdTQcGJ , fXGe GdGbJWGYGJ ef GdeUOQ , GdYbhHGJ GdGYGfGJ h GdGYaGAGJ eY OQGSI ejOGfjI dTNU WHjYj h eYfhj MSH GdMGdI GdVQjHjI , fXGe GdGgJdGcGJ , GdeQGbHI h GdefGRYGJ (B: (3cjajI GLQGA GdeQGbHI HGdfSHI ddVQjHI Ydi GdONd GdGLeGdj h GdVQjHI Ydi CQHGM GdTQcGJ(B.s
Keywords: (3GdCQHGMs; (3GdTQcGJs; (3GdVQjHIs; (3VQjHI GdTQcGJs